Navigating Challenges and Transforming Radio Journalism in Indonesia: from New Order Control to Reform Opportunities - Widodo, Yohanes; Abrar, Ana Nadhya; Adiputra, Wisnu Martha (Jurnal The Messenger, 2024)
Introduction: The evolution of radio journalism in Indonesia provides critical insights into its historical, technological, cultural, and political significance. As a medium, radio has been a cornerstone of public discourse and democratization, particularly during transformative periods such as the Reform Era. This study examines the evolution and contemporary challenges of radio journalism, with a specific focus on the operational realities of private radio stations in Indonesia. Methods: This research adopts a mixed-methods approach, combining in-depth interviews with radio managers and surveys targeting radio station managers. It provides a comprehensive analysis of the factors influencing the sustainability, quality, and adaptability of radio journalism. Findings: The findings indicate that increased press freedom has facilitated more diverse and independent journalistic practices. However, the sector faces significant challenges in adapting to the demands of a rapidly evolving media ecosystem. Digital disruption has created an urgent need for multi-platform strategies, yet many stations lack the technical expertise and resources required for full adaptation. Additionally, the scarcity of trained journalists and editorial teams limits the production of high-quality, independent journalism, undermining public trust in radio as a credible medium. Originality: This study presents a groundbreaking exploration of the evolution of radio journalism in Indonesia, offering a comprehensive perspective that seamlessly intertwines its historical roots with the pressing challenges of the modern media era. By examining the sector’s regulatory and economic pressures, it sheds light on the structural and operational hurdles faced by radio journalism while uncovering innovative strategies for navigating the disruptive forces of digital transformation.